1986
DOI: 10.1055/s-2008-1025727
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Eight Weeks of Bicycle Ergometer Sprint Training on Human Muscle Buffer Capacity

Abstract: This investigation was undertaken to determine whether human skeletal muscle buffer capacity (BCm) is affected by training. Eight untrained males participated in 8 weeks of sprint training on bicycle ergometers. Muscle biopsy samples were taken from the vastus lateralis before and at several times following an incremental bicycle ergometer test (0 min, 5 min, 15 min). These subjects were tested before (PRE) and following (POST) the training period. Seven endurance-trained cyclists (ET) were also tested for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
96
3
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(114 citation statements)
references
References 19 publications
14
96
3
1
Order By: Relevance
“…Our results suggest that the aerobic high-intensity interval training with rollerski promote increases in anaerobic capacity in cross-country skiers. This finding corroborate that of Sharp et al [1986] [25], who reported that high-intensity sprint training has significant influences in anaerobic energy production and power production. To understand the importance of the aerobic and anaerobic capacity in sprint skiing is still need more research [9].…”
Section: Discussionsupporting
confidence: 92%
“…Our results suggest that the aerobic high-intensity interval training with rollerski promote increases in anaerobic capacity in cross-country skiers. This finding corroborate that of Sharp et al [1986] [25], who reported that high-intensity sprint training has significant influences in anaerobic energy production and power production. To understand the importance of the aerobic and anaerobic capacity in sprint skiing is still need more research [9].…”
Section: Discussionsupporting
confidence: 92%
“…This finding is supported by increases in the muscle buffer capacity in response to high-intensity interval training (35). In addition, sprint training has been reported to increase the muscle buffer capacity, whereas endurance training showed no effect (36). Presumably, the anaerobic training stimulus for team sport athletes may have been to enhance the ICB phase, which may be attributable to the improvement of the buffering capacity as the contributing factor to the tolerance of high-intensity exercise.…”
Section: Discussionmentioning
confidence: 87%
“…This reaction accounts for a significant portion of the theoretical buffering capacity of hydrogen ions in exercising muscle (35). The accumulation of hydrogen ions has been proposed as a possible cause of muscle fatigue (26).…”
Section: The Reactions Of the Phosphagen Systemmentioning
confidence: 99%
“…Some researchers suggest that the PCr concentration in muscle is increased by endurance training (4,11,40). Other findings suggest that the PCr level may be enhanced by sprint training (10,35) or find no change in muscle creatine concentration with sprint training (17). Furthermore, sprint training induces hypertrophy, which should cause an increased total creatine concentration of muscle.…”
Section: Training and Pcrmentioning
confidence: 99%